2010
DOI: 10.1007/s00244-010-9580-8
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Cadmium on Steroid Hormones and Their Receptors in Women with Uterine Myomas

Abstract: Cadmium (Cd) is one of the environmental metalloestrogens, and its role in uterine tissues has not yet been fully elucidated. The aim of the study was to investigate estrogenic properties of Cd in uterine tissues by analyzing the expression of estrogen receptor (ER) and progesterone receptor (PR) as well as estrogen and progesterone levels in serum and Cd concentrations in blood and tissues. The samples of tissues (leiomyoma and surrounding myometrium) collected intrasurgically and blood samples drawn from 53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…The levels of cadmium accumulated in the myometrium surrounding the neoplastic tissue were higher than in the neoplastic tissue itself, which probably results from the fact that these are fast growing tissues. In our earlier studies, statistical analysis also demon strated a significant correlation between BCd concentration and Cd level in uterine tissues [8,15]. Apart from the effect on internal organs, cadmium may also destroy the vascular endothelium, one of the primary targets of Cd toxicity [34,35].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The levels of cadmium accumulated in the myometrium surrounding the neoplastic tissue were higher than in the neoplastic tissue itself, which probably results from the fact that these are fast growing tissues. In our earlier studies, statistical analysis also demon strated a significant correlation between BCd concentration and Cd level in uterine tissues [8,15]. Apart from the effect on internal organs, cadmium may also destroy the vascular endothelium, one of the primary targets of Cd toxicity [34,35].…”
Section: Discussionmentioning
confidence: 87%
“…Due to the endocrine-disrupting properties of cadmium [10], it has been suggested that environmental exposure to it may cause estrogen-dependent diseases such as breast cancer and endometrial cancer [11][12][13]. Moreover, although uterine myomas belong to the group of hormone-dependent tumors, the participation of cadmium in their etiology has not been fully explained [14][15][16]. Our earlier studies on women with myoma and endometrial cancer showed the accumulation of cadmium in the affected tissues.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Still, past research has demonstrated a correlation between estrogen receptor expression and cadmium concentration within uterine myomas, suggesting this metal may contribute to the growth of fibroids through estrogen receptor activation. Whole blood cadmium concentrations have correlated well with concentrations in leiomyoma tissue [35]. …”
Section: Discussionmentioning
confidence: 99%
“…While it is feasible that fibroids may serve as tissue reservoir, at present there are no data on trace element uptake within leiomyomas to corroborate this hypothesis. One small study found decreased concentrations of cadmium [35] and iron in leiomyomata compared with normal uterine muscle, and increased magnesium and Mg/Ca ratio [42]. Concentrations of zinc and copper in leiomyoma were not significantly different from those in surrounding normal myometrium [43].…”
Section: Discussionmentioning
confidence: 99%